Cholecalciferol supplementation to improve the hepatitis B vaccination response in hemodialysis patients: A first randomized open label pilot study (DeVitaHep). Issue 52 (20th December 2021) - Hafner-Giessauf, Hildegard; Horn, Sabine; Schwantzer, Gerold; Sprenger-Mähr, Hannelore; Lhotta, Karl; Rosenkranz, Alexander R.; Zitt, Emanuel
Abstract: Background: Patients with advanced chronic kidney disease should be vaccinated against hepatitis B. In observational studies vitamin D insufficiency is associated with a reduced seroconversion rate. The effect of cholecalciferol supplementation on hepatitis B vaccination response in haemodialysis patients with vitamin D insufficiency is unknown. Methods: In this randomized open label pilot study 40 unvaccinated haemodialysis patients with 25(OH)D insufficiency (<30 ng/mL) were enrolled. In the supplementation group, we administered cholecalciferol orally in a dose of 28, 000 IU weekly for a maximum of 12 weeks. Hepatitis B vaccination (HBvaxPRO 40 µg i.m. months 0, 1, 6) was performed after achieving a 25(OH)D level >30 ng/mL or after completing three months of supplementation despite failure to achieve the target level. In the control group, patients were vaccinated immediately after randomization. Anti-hepatitis B-antibody titer (anti-HBs) was measured eight weeks after completing the vaccination course. Results: Thirty-seven (26 male, 11 female) patients aged 65 (13.5) years underwent randomization with 17 patients allocated to the control group and 20 patients included in the supplementation group. After 12 weeks of cholecalciferol supplementation, mean (SD) 25(OH)D concentration increased from 15.0 (8.0) to 31.0 (7.1) ng/mL, but remained unchanged in the control group (14.0 (7.1) to 11.6 (7.5) mg/mL). Neither the number of patients with seroconversion (anti-HBs titer ≥ 10 IU/L; n = 6 (35.3%) vs n = 3 (27.3%), p = 0.704), nor the number of patients with seroprotection (anti-HBs titer >100 IU/L; n = 4 (23.5%) vs n = 2 (18.2%) differed between treatment groups. Cholecalciferol supplementation was safe without treatment-related adverse events. Conclusion: In this small pilot study, high-dose oral cholecalciferol supplementation did not improve the hepatitis B vaccination response in haemodialysis patients with vitamin D insufficiency. This clinical trial was registered within EudraCT (EudraCT number 2011-004621-26).